The Prevalence of Gender-based Violence and Harmful Traditional Practices against Women in the Tigray Region, Ethiopia. (February 2020) - Gebre, Tewelde; Hagos, Fana; Teklu, Gebreyesus; Fisseha, Mekonnen; Abera, Mesele
In Ethiopia, large numbers of women are at higher risk of gender-based violence and harmful traditional practices. The main aim of the study is to explore the prevalence rate of gender-based violence and harmful traditional practices against women in the Tigray region, Ethiopia. In this study, a total of 1253 women were surveyed, of which 560 were from rural areas. Further, 14 focus group discussions and in-depth key informant interviews were conducted with relevant governmental and non-governmental bodies. It was found that a significant number of married women were not asked for their permission to be married and their mate was mostly selected by their family. Among others, age was found to be a statistically significant predictor for early marriage and permission of girls to get married with an odds ratio of 0.95 and 0.97, respectively ( p < 0.05). Twenty-one forms of gender-based violence and 29 forms of harmful traditional practices and stereotypes against women were identified. These practices were mostly supported by the community. While gender-based violence was found to be somewhat higher in urban areas, most of the harmful traditional practices were slightly higher in rural areas.